2020
DOI: 10.1021/acs.chemrestox.0c00375
|View full text |Cite
|
Sign up to set email alerts
|

Predicted AS3MT Proteins Methylate Arsenic and Support Two Major Phylogenetic AS3MT Groups

Abstract: Inorganic arsenic is one of the most toxic and carcinogenic substances in the environment, but many organisms, including humans, methylate inorganic arsenic to mono-, di-, and trimethylated arsenic metabolites, which the organism can excrete. In humans and other eukaryotic organisms, the arsenite methyltransferase (AS3MT) protein methylates arsenite. AS3MT sequences from eukaryotic organisms group phylogenetically with predicted eubacterial AS3MT sequences, which has led to the suggestion that AS3MT was acquir… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(6 citation statements)
references
References 39 publications
0
6
0
Order By: Relevance
“…ArsMs with three domains have a relatively low arsenic methylation activity, converting 15–42% of As­(III) into methylated species (Table ). One exception is the thermophilic CmArsM, which produces 66% methylated species and with DMAs­(V) as the primary product at 70 °C, perhaps because rates of catalysis are generally higher at elevated temperatures. (Again, the actual products are likely trivalent but are oxidized in air or during analysis.)…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…ArsMs with three domains have a relatively low arsenic methylation activity, converting 15–42% of As­(III) into methylated species (Table ). One exception is the thermophilic CmArsM, which produces 66% methylated species and with DMAs­(V) as the primary product at 70 °C, perhaps because rates of catalysis are generally higher at elevated temperatures. (Again, the actual products are likely trivalent but are oxidized in air or during analysis.)…”
Section: Resultsmentioning
confidence: 99%
“…ArsMs from different organisms show different methylation efficiencies and can be classified into two groups . Three-domain ArsMs in Group 1 exhibit low arsenic methylation activity and produce little volatile TMAs­(III).…”
Section: Introductionmentioning
confidence: 99%
“…Urinary arsenobetaine, trimethylarsine oxide, and arsenocholine were separated on a cation exchange chromatography column (Nucleosil SCX, Skandinaviska Genentch AB, Sweden) by HPLC and ICP-MS (7700x Agilent), as described previously (Reid et al, 2020;Xie et al, 2006;Torbøl Pedersen et al, 2020). The average LOD of 10 analyses were 0.27 μg/L for arsenobetaine and 0.28 μg/L for arsenocholine.…”
Section: Analysis Of Trace Elementsmentioning
confidence: 99%
“…A study led by Seth Walk, an associate professor of microbiology and cell biology at Montana State University, found that a healthy human microbiome transferred into germ-free As3mt knockout mice via fecal transplant completely protected the mice against the lethal effects of acute iAs exposure. 48 This was partially due to the activity of the arsenic methyltransferase ( ArsM ) gene cluster 58 —the bacterial analog of the human AS3MT gene—in the common gut microbe Faecalibacterium prausnitzii. 48 …”
Section: Metabolism By Human and Microbial Enzymesmentioning
confidence: 99%
“…The geologic contamination of drinking water has existed for a very long time, whereas human-caused increases in atmospheric Hg are more recent. This difference, says Broberg, may explain the evolution of the AS3MT defense system in many species 58 , 75 , 76 and the lack of an analogous MeHg system. “I find it very interesting that the same arsenic defense system exists in bacteria and humans because this is not the case for many other environmental chemicals,” she says.…”
Section: Variations In Toxicitymentioning
confidence: 99%